Intelectuales en plataformas: aportes teóricos, alcances y límites para la praxis - Gomes Nascimento, Letycia (2024)
Observing the transformations articulated in society, culture and communication, with an emphasis on the expanded use of digital platforms in the subjects’ daily lives, this paper seeks to present central theoretical premises to categorize the notion of platformized intellectual in contrast with the presence of digital influencers in social media. Starting mainly from the theoretical framework developed by Antonio Gramsci to define the intellectual and his political praxis, we discuss the characteristics of this subject and his field of action in a platformized society. Based on a theoretical debate and an exploratory documentary research, we discuss the potential, limitations and strategies of intellectual activity in a platformized society seeing how their creations work as a form political education.